2020
DOI: 10.1186/s43556-020-00014-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing inhaled protein therapeutics for lung diseases

Abstract: Biologic therapeutics such as protein/polypeptide drugs are conventionally administered systemically via intravenous injection for the treatment of diseases including lung diseases, although this approach leads to low target site accumulation and the potential risk for systemic side effects. In comparison, topical delivery of protein drugs to the lung via inhalation is deemed to be a more effective approach for lung diseases, as proteins would directly reach the target in the lung while exhibiting poor diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 101 publications
0
53
0
Order By: Relevance
“…To benchmark the newly implemented CVS-STEOM-CCSD method's accuracy, we have used the small molecule test set of Mathews 82 for which EOM-CCSDT results have been reported. The test set consists of five molecules H2O, CO, NH3, HCN, and C2H4, with a total of 28 core excited states.…”
Section: Resultsmentioning
confidence: 99%
“…To benchmark the newly implemented CVS-STEOM-CCSD method's accuracy, we have used the small molecule test set of Mathews 82 for which EOM-CCSDT results have been reported. The test set consists of five molecules H2O, CO, NH3, HCN, and C2H4, with a total of 28 core excited states.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, DARPin molecules demonstrate excellent temperature stability, which might enable alternative routes of administration, such as inhalation described for other highly stable protein scaffolds( 47,48 ). The simple molecular architecture of multivalent DARPin molecules allows manufacturing in bacterial expression systems at very high yields which leads to cost-effective and scalable production of antiviral biologicals at industrial quantities (supplementary Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The use of nanoparticles as delivery systems allows for a reduction in antibody dosing, increases area of coverage, reduces immunogenicity, and controlled release (Sousa et al 2017 ). However, the half-life of inhaled Abs in humans is approximately 16–24 h (~ 1 day) (Koussoroplis et al 2014 ; Matthews et al 2020 ). The encapsulation of antibodies in nanoparticles allows for the slow release of these antibodies, resulting in an increase in their overall bioavailability.…”
Section: Challenges and Advancements Associated With Antibody-based Prevention And Therapeutic Approaches For Inhaled Deliverymentioning
confidence: 99%
“…Gai et al ( 2020 ) have shown that a nanobody developed against the nCOV-19 showed high stability post-nebulisation. To increase antibody retention in respiratory mucosa, Zhang et al ( 2020 ) engineered a human antibody that recognises SARS-CoV-2 S1 spike protein with a higher affinity for mucin and was found to be effective in both nasal and lung areas 7 days after viral exposure in a mouse model (Matthews et al 2020 ). Other concerns include the possibility of immunogenicity of antibodies used in the nasal spray due to the anticipated long-term frequent use as prophylaxis.…”
Section: Challenges and Advancements Associated With Antibody-based Prevention And Therapeutic Approaches For Inhaled Deliverymentioning
confidence: 99%